Sensorimotor mismatch disrupts motor automaticity and increases anxiety during a goal-directed balance task - Hua, Anke; Westlake, Kelly P.; Bonnet, Cédrick T.; Wang, Jian (Frontiers in Human Neuroscience, 2025)
IntroductionSensorimotor integration is crucial role for goal-directed tasks, with sensorimotor mismatch impairing movement execution and potentially evoking anxiety. However, the relationship between mismatch-induced anxiety, movement precision, and automaticity remains unexplored. This study investigated the effect of sensorimotor mismatch on voluntary postural control during goal-directed tasks and the relationship between sensorimotor mismatch-induced anxiety and motor performance.MethodsTwenty-three young, injury-free adults performed a precision task requiring center of pressure (COP) control within a limited screen area under congruent (aligned visual inputs and motor outputs) and incongruent (180-degree mismatch between visual feedback and motor actions) conditions. Self-reported anxiety was assessed using a seven-point Likert scale. Motor performance was quantified using COP area, total path length and sample entropy of COP trajectory for movement precision and automaticity.ResultsSensorimotor mismatch significantly increased self-reported anxiety (p = 0.02) and reduced movement automaticity, evidenced by lower sample entropy values (p < 0.01). Higher anxiety scores were correlated with decreased movement automaticity in the medio-lateral direction (lower sample entropy) under the mismatch condition (r = −0.33, p = 0.008).DiscussionThese findings suggest that sensorimotor mismatch induces self-perceived anxiety and disrupts automatic motor control processes.